Mitigation of FWM crosstalk in WDM system using polarization interleaving technique - Abd H.J.; Din N.M.; Al-Mansoori M.H.; Abdullah F.; Fadhil H.A. (2023)
In long-haul transmission systems, optical transmission characteristics are degraded by four-wave mixing (FWM) generated in optical fibers. This paper presents a new approach to reduce the four wave mixing crosstalk based on polarization interleaving is presented. The FWM behavior and the performance of WDM systems were analyzed using the proposed technique. The simulation was performed using different power values with 100 GHz channel spacing, and at a data rate of 60Gb\s. It was found that the FWM power was drastically reduced to -64 dBm when the polarization technique was used. In addition, the WDM system performance showed that at the sixth channel (192 THz), the suggested approach incurred a BER of 4.8610-21, in comparison with the absence of the approach where the BER was 4.310-10 at the same received power. The results prove that the proposed system is superior in mitigating FWM crosstalk. 2013 IEEE.